Marine Macro-and Microplastic Litter Along The Coastal Area of Kuala Perlis - Odli, Zaity Syazwani Mohd; Lee, Anisah Jessica; Asari, Muhamad Amiruddin (European Publisher, 2019)
Marine litter along the coastal area has long been a threat to the ecosystem and one of the crucial issues repeatedly in debates. Since the study of marine litter is at its infant stage in Malaysia, this research took the initiative to focus on coastal pollution with the objective to ascertain the amount of different categories of macro marine litter, to determine the amount of microplastic in the sediment layer, and to determine the possible correlation between macroplastic abundance and microplastic amount in the sediment layer. The study area is the coastal region of Kuala Perlis, Malaysia. Macro marine litter is collected at four sampling sites along the shoreline stretching 100 m in length and divided by four sections in width. A quadrat of 50 cm x 50 cm is used to collect sediment from surface to 5 cm depth for microplastic analysing. The total weight of macroplastics collected is 27.79 kg with highest amount being plastic weighing 20.1 kg, fabric (6.96 kg), glass (0.53 kg) and rubber (0.2 kg), while wood and metal were unfound. The amount of macroplastic, being the most collected, proved the reason it becomes a major threat. This study found the amount of microplastics ranged between 0.000096 to 0.000160 kg/m3, while macroplastics ranged between 0.00167 to 0.00402 kg/m2. Result shows a significant relationship (R2 of 0.9328) between macro and microplastic at 95% significance level. The linear regression equation computed is y = 26.388x + 0.051, with y representing microplastic (kg/m2) while x represents macroplastic (kg/m2).